Qualidade das silagens de sorgo e de planta inteira de soja na terminação de cordeiros em confinamento - Protes, Verena Micheletti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this research was to evaluate the effect of using whole-plant soybean silage (WPSS) compared to sorghum silage (SOS) in diet for finishing crossbred lambs on performance, carcass characteristics, meat quality and economic performance. The soybean used was the BMX Power RR, sown 3 cm deep and density of 400,000 seeds / he, spaced 0.45 m. The mechanical harvesting of silage mass was done when the soybean plants reached the reproductive stage R7, the height of 10-15 cm from the ground level, using two line shelf reduced average spacing between lines of 0.50 m and the cut material into particles averaging 4 mm. The experimental design was completely randomized with two treatments and 14 repetitions, one of a conventional diet for lambs in confinement with SOS and the other with WPSS as roughage. The animals with early weight of 20 ± 2 kg were randomly assigned to each treatment, housed in individual pens with free access to the trough and water, were slaughtered when they reached the average weight of 32 kg. There was no significant difference (P <0.05) between treatments for the performance parameters, economic evaluation, carcass quality and meat, except for shear force, where the animals fed WPSS had higher meat tenderness. There was no difference for most fatty acids found in meat, except for the six fatty acids: 0, 14: 1, 20: 0; 16: 0, 16: 1 found in larger amounts in meat of sorghum treatment and fatty acid 18: 2n6c and 18: 1n9t in larger amounts in meat of soybean treatment. Animals fed with WPSS had a lower amount of acid hypercholesterolemic (16: 0, 14: 1, 16: 1) and higher concentrations of omega 6 in their meat. The WPSS can be a alternative of roughage to finishing lambs in confinement because no negative effect on animal performance, and have provided a beef with superior softness, fewer harmful acids to health and higher amounts of omega 6.

O trabalho de pesquisa teve por objetivo avaliar o efeito da utilização de silagem de planta inteira de soja (SPS) em comparação à silagem de sorgo (SSO) em dieta para terminação de cordeiros cruzados, sobre o desempenho, características de carcaça, qualidade da carne e desempenho econômico. A cultivar de soja utilizada foi a BMX Potência RR, semeada a 3 cm de profundidade e densidade de 400.000 sementes/ha, no espaçamento de 0,45 m. A colheita mecânica da massa para ensilagem foi realizada quando as plantas de soja atingiram o estádio reprodutivo R7, na altura de 10-15 cm em relação ao nível do solo, utilizando plataforma de duas linhas com espaçamento reduzido médio de 0,50 m entre linhas sendo o material picado em partículas médias de 4 mm. O delineamento experimental foi inteiramente casualizado, com dois tratamentos e 14 repetições, sendo um constituído por uma dieta convencional de confinamento de cordeiros a base de SSO e a outra por SPS como volumoso. Os animais com peso médio inicial de 20±2 kg foram distribuídos aleatoriamente em cada tratamento, alojados em baias individuais com acesso livre ao cocho e à água, sendo abatidos ao atingirem o peso vivo médio de 32 kg. Não houve diferença significativa (P<0,05) entre os tratamentos para os parâmetros de desempenho, avaliação econômica, qualidade da carcaça e da carne, exceto para força de cisalhamento, sendo que os animais alimentados com SPS apresentaram maior maciez da carne. Não houve diferença para a maioria dos ácidos graxos encontrados na carne, exceto para os ácidos graxos 6:0, 14:1, 20:0; 16:0, 16:1, encontrados em maior quantidade na carne do tratamento de sorgo e para os ácidos graxos 18:2n6c e 18:1n9t em maior quantidade na carne do tratamento de soja. Animais alimentados com SPS apresentaram menor quantidade de ácidos hipercolesterolêmicos (16:0, 14:1, 16:1) e maiores concentrações...
Keywords: Ovino - Alimentação e rações; Sorgo - Silagem; Carne - Qualidade; Sheep